Reduced L-type calcium current in ventricular myocytes from pigs with hyperdynamic septic shock - Štengl, Milan; Barták, František; Sýkora, Roman; Chvojka, Jiří; Beneš, Jan; Kroužecký, Aleš; Novák, Ivan; Švíglerová, Jitka; Kuncová, Jitka; Matějovič, Martin (Critical care medicine, 2010)
OBJECTIVE: To hypothesize that reduced L-type calcium current with consequent shortening of cardiac repolarization is present in a clinically relevant porcine model of hyperdynamic septic shock. Myocardial depression is a well-recognized manifestation of sepsis and septic shock. Reduction of L-type calcium current was demonstrated to contribute to the myocardial depression in endotoxemic rodents. DESIGN: Laboratory animal experiments. SETTING: Animal research laboratory at a university. SUBJECTS: Twenty-two domestic pigs of either gender. INTERVENTIONS: In anesthetized, mechanically ventilated, and instrumented pigs, sepsis was induced by bacteremia (central venous infusion of live Pseudomonas aeruginosa) and continued for 22 hrs. MEASUREMENTS AND MAIN RESULTS: Electrocardiogram was recorded before and 22 hrs after induction of bacteremia. RR, QT, and QTc intervals were significantly shortened by sepsis. In vitro, action potentials were recorded in right ventricular trabeculae. Action potential durations were shortened in septic preparations. Tumor necrosis factor-alpha did not influence action potential durations. L-type calcium current was measured in isolated ventricular myocytes. Peak L-type calcium current density was reduced in myocytes from septic animals (8.3 +/- 0.4 pA/pF vs. 11.2 +/- 0.6 pA/pF in control). The voltage dependence of both L-type calcium current activation and inactivation was shifted to more negative potentials in myocytes from septic animals. Action potential-clamp experiments revealed that the contribution of L-type calcium current to the septic action potential was significantly diminished. In cardiac myocytes incubated with tumor necrosis factor-alpha, L-type calcium current was not further affected. CONCLUSIONS: In a clinically relevant porcine model, hyperdynamic septic shock induced shortening of ventricular repolarization and reduction of L-type calcium current. The contribution of L-type calcium current to the action potential in septic ventricular myocytes was significantly diminished. Tumor necrosis factor-alpha probably did not contribute to this effect.
Keywords: elektrokardiografie; Calcium Channels, L-Type; akční potenciály; Action Potentials; Shock, Septic; Tumor Necrosis Factor-alpha; vápník; Disease Models, Animal; mužské pohlaví; srdeční komory; Sus scrofa; vápníkové kanály - typ L; Myocytes, Cardiac; TNF-alfa; Calcium; Electrocardiography; modely nemocí na zvířatech; ženské pohlaví; zvířata; Heart Ventricles; kardiomyocyty; Female; septický šok; Male; Animals